Nicotine promotes breast cancer metastasis by stimulating N2 neutrophils and generating pre-metastatic niche in lung - Tyagi, Abhishek (Nat Commun, 2021)
Smoking has a profound impact on tumor immunity, and nicotine, which is the major addictive component of smoke, is known to promote tumor progression despite being a non-carcinogen. In this study, we demonstrate that chronic exposure of nicotine plays a critical role in the formation of pre-metastatic niche within the lungs by recruiting pro-tumor N2-neutrophils. This pre-metastatic niche promotes the release of STAT3-activated lipocalin 2 (LCN2), a secretory glycoprotein from the N2-neutrophils, and induces mesenchymal-epithelial transition of tumor cells thereby facilitating colonization and metastatic outgrowth. Elevated levels of serum and urine LCN2 is elevated in early-stage breast cancer patients and cancer-free females with smoking history, suggesting that LCN2 serve as a promising prognostic biomarker for predicting increased risk of metastatic disease in female smoker(s). Moreover, natural compound, salidroside effectively abrogates nicotine-induced neutrophil polarization and consequently reduced lung metastasis of hormone receptor-negative breast cancer cells. Our findings suggest a pro-metastatic role of nicotine-induced N2-neutrophils for cancer cell colonization in the lungs and illuminate the therapeutic use of salidroside to enhance the anti-tumor activity of neutrophils in breast cancer patients.